Clovis Nazareno and his poetic imagination of Bohol - Gabriel, Iris Valerie Domingo (Animo Repository, 2004)
This thesis analyzes nineteen poems from the Palanca Prize winner collection, The Link Immemorial, by Clovis L. Nazareno, using Gaston Bachelard's theory on the Poetics of Space. The issues on nostalgia, romance, the pain of losing, the imagine Bohol, are examined in this research revealing how the author represents the real, concrete Bohol. It will uncover how Clovis Nazareno as a native poet finds himself in his own poetic imagination. The analysis focuses on what must be the author's specific and concrete way of imagining Bohol. The book of Gaston Bachelard describes the house in its specificities such as the cellar, attic, drawers, and corners and so on. Several chapters from the Poetics of Space will be discussed to uncover the meaning behind the poems. It will also focus on how the author relates the thematic patterns evident in the poems with the real issues in life. What makes Bohol beautiful is not just its historical past or its tourist attractions, but it is beautiful for the reason that Boholanos themselves have this certain inner character, intimate beauty, that is found justly in their souls as well as having more to it than just being an island.